Identifying patients at risk of perinatal mood disorders. - Topiwala, A; Hothi, G; Ebmeier, K (2012)
Perinatal mental illness influences obstetric outcomes, mother-baby interactions and longer term emotional and cognitive development of the child. Psychiatric disorders have consistently been found to be one of the leading causes of maternal deaths, often through suicide. Postnatal depression and puerperal psychosis are two disorders most commonly associated with the perinatal period. The most efficient strategy to identify patients at risk relies on focussing on clinically vulnerable subgroups: enquiries about depressive symptoms should be made at the usual screening visits. Attention should be paid to any sign of poor self-care, avoidance of eye contact, overactivity or underactivity, or abnormalities in the rate of speech. Particular care should be taken to ask about suicidal ideation and thoughts of harming others, including the baby. One of the most important risk factors is a previous history of depression. The degree of risk is directly correlated with severity of past episodes. Both antenatal and postnatal depression are being increasingly recognised in men. Puerperal psychosis is rare (1 to 2 per 1,000). Sixty per cent of women with puerperal psychosis already have a diagnosis of bipolar disorder or schizoaffective disorder. Women with a personal history of postpartum psychosis or bipolar affective disorder should be considered as high risk for postpartum psychosis. All pregnant women who are identified as being at high risk should have a shared care plan for their late pregnancy and early postnatal psychiatric management. Women with current mood disorder of mild or moderate severity who have a first-degree relative with a history of bipolar disorder or postpartum psychosis should be referred for psychiatric assessment.